IMPLEMENTASI PENGADAAN BAHAN PUSTAKA DI PERPUSTAKAAN PERGURUAN TINGGI STUDI PADA PERPUSTAKAAN UNIVERSITAS BRAWIJAYA - Kethy Hariyadi Putri (Central Library of Universitas Sebelas Maret, 2017)
Acquisition of library materials is one of the core activities in the collection development. Therefore,the implementation requires a good planning. The purposes of this research are to find out about the implementation of library materialsacquisition in the Library of Brawijaya University along with the obstacles faced in the process of acquisition of the library materials. The method used in this research are observation, interview, and documentation. The results found that the acquisition’s team managesthe library materials selection, the library materials acquisition, and the inventory process of the library materials. These activities are carried out by the collection development subfield. The acquisition of the library materials obtained from purchases and gifts/donations. Long bureaucracy, limited funds, discrepancies between library materials ordered with library materials received, and limited human resources allegedly become obstacles in the procurement of library materials in the Library of BrawijayaUniversity.